Pengaruh Kualitas Produk Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Di Sushi Den Bandung - Anggraeni, Devi; Sudono, Agus; Turgarini, Dewi (Universitas Pendidikan Indonesia, 2015)
Customer satisfaction is the most important thing in the catering business.Â Customer satisfaction affect the profit earned by entrepreneur food. Things that canÂ affect customer satisfaction among them is the quality of product and quality ofÂ services provided by the food producers.One way to determine customer satisfactionÂ is to compare the expectation and the reality perceived by the customer.Research method used in this research is descriptive verification method. TheÂ number of samples in this research were 100 consumers, data collection is done byÂ spreading the questionnaire and documentary study. Model analysis of the data usedÂ is multiple linear regression using SPSS 22 for windows. The results showed that theÂ Product Quality and Service Quality has significant impact on customer satisfaction.Â Results of calculations using multiple linear regression analysis obtain the equationÂ Y=3,291+0,059Xâ‚+0,152Xâ‚‚ it means an increase by 1 unit Product Quality, theÂ Consumer Satisfaction Sushi Den Bandung will increase by 0.059 and any increaseÂ Quality of Service by 1 unit, the Consumer Satisfaction Sushi Den Bandung will alsoÂ rise by 0.152. Food producers should further improve the quality of product qualityÂ and service quality by determining and implementing the Standard OperationalÂ Procedure properly in order to provide a positive impact for food company.